BCG induces protection against Mycobacterium tuberculosis infection in the Wistar rat model. - Amit Singhal; Vanessa Mathys; Mehdi Kiass; Colette Creusy; Baptiste Delaire; El Moukhtar Aliouat; Véronique Dartois; Gilla Kaplan; Pablo Bifani (PLoS ONE, 2011)
Our understanding of the correlation of Mycobacterium bovis Bacille Calmette-Guerin (BCG)-mediated immune responses and protection against Mycobacterium tuberculosis (Mtb) infection is still limited. We have recently characterized a Wistar rat model of experimental tuberculosis (TB). In the present study, we evaluated the efficacy of BCG vaccination in this model. Upon Mtb challenge, BCG vaccinated rats controlled growth of the bacilli earlier than unvaccinated rats. Histopathology analysis of infected lungs demonstrated a reduced number of granulomatous lesions and lower parenchymal inflammation in vaccinated animals. Vaccine-mediated protection correlated with the rapid accumulation of antigen specific CD4(+) and CD8(+) T cells in the infected lungs. Immunohistochemistry further revealed higher number of CD8(+) cells in the pulmonary granulomas of vaccinated animals. Evaluation of pulmonary immune responses in vaccinated and Mtb infected rats by real time PCR at day 15 post-challenge showed reduced expression of genes responsible for negative regulation of Th1 immune responses. Thus, early protection observed in BCG vaccinated rats correlated with a similarly timed shift of immunity towards the Th1 type response. Our data support the importance of (i) the Th1-Th2 balance in the control of mycobacterial infection and (ii) the value of the Wistar rats in understanding the biology of TB.